ORGANIZATIONAL AND ECONOMIC MECHANISM OF ENSURING EFFECTIVE FUNCTIONING OF SMALL BUSINESS STRUCTURES OF THE REGION - Irina Ponomareva; Dmitry Maksimov; Michael Chernyshev (Вестник Северо-Кавказского федерального университета, 2022)
Development of effective mechanisms of the small business structures of the region providing steady functioning is the actual direction of modern development of many national economic systems, including development of the organizational and economic mechanisms providing synergetic effect of economic activity of small business structures of the region in conditions of membership of Russia in the WTO.